The effects of glass waste and grog on physical and mechanical properties in porcelain by powder pressing method - Aramjat, Abu Bakar (2014)
This research aims to study and investigate the effects of glass waste and grog on physical and mechanical properties in porcelain by using pressing method. Soda lime silicate glass is used as fluxing agent and fired ceramic (grog) act as filler in porcelain body fabrication. Firstly, the recycle glass waste (glass window) and fired glazed tiles were crushed by using disc crusher until they passed through a sieve of less than 53μm. The glass powder and gr0g was than mixed with based porcelain body {5-0% kao-1-in, 25% feldasapr and 25% silica) with different percentage (5%glass-20% grog, 10%glass-15% grog, 15%glass-10% grog and 20%g]ass-5% grog). Then, green ceramic article is formed using uniaxial dry pressing method. All waste materials were analysed on their thermal behavior, chemical composition and mineralogical phase. In this study, the sintering temperature are varied at l 150°C, 1200°C, 1250°C, and 1280°C. The microstructure and phase present in sinterd products is analyzed using optic microscope, scanning electron microscope (SEM) and x-ray diffraction (XRD).The physical properties are determined using apparent porosity, bulk density and water absorption test. Mechanical analysis is carried out using modulus of rupture to determine its mechanical properties. Tue results shown that the sintering temperature of porcelain decrease with the decreasing in percentage glass waste in composition. Hence, it will decrease the water absorption and porosity of the porcelain. The physical-mechanical properties of porcelain will be affected by the sintering temperature, where physical-mechanical properties will be decreasing when the temperature reach at the optimum value (l 200°C). The best formulation composition is G5T20 (5% glass waste and 20% grog) and the optimum firing at 1200°C. Through the study, the enhancement of fabricated porcelain could be applied to the structural (such as floor and wall tile) applications through the advantage of mechanical and physical properties by high performance of strength, low water absorption, low porosity and high bulk density.